Major element geochemical variations in a Miocene-Pliocene Siwalik paleosol sequence: Implications to soil forming processes in the Himalayan foreland basin - Kumaravel, V.; Sangode, S.J.; Siddaiah, N. Siva; Kumar, Rohtash (My University, 2009)
Elemental mobility based on major element geochemistry from 58 horizons related to six paleosols profiles in a typical Miocene — Pliocene Siwalik fluvial sequence in the NW Himalaya has been reported here. The paleosols developed over felsic parent material of fine to medium grained sandstone indicate notable enrichment of sesquioxides (Al2O3 = 29 % and Fe2O3 = 54 %) depicting significant leaching and dissolution. The depletion of base cations (mean wt% of Na2O = 0.24; CaO = 0.51) and SiO2 (mean wt% = 63.6) in the pedogenic layers and its enrichment in the parental material (mean wt% of Na2O = 0.44; CaO = 1.3; SiO2 = 70.1) shows a good gradient of elemental mobility due to pedogenesis. Bivariate plots of the base ratios (Na2O/K2O, CaO/K2O, and MgO/K2O) vs. Al2O3 reveal independent distribution for parent material, pedogenic horizons and the incipient zone indicating the gradual addition/removal of immobile/mobile elements with varying pedogenesis. Discontinuous and segmented pattern of the geochemical parameters enables discrimination of multiple pedogenic episodes and recognition of soil welding processes in the multistorey composite paleosols. We also test the applicability of the geochemical climofunctions: the Mean Annual Precipitation (MAP) and Mean Annual Temperature (MAT); that demands more data for calibration in the Siwalik paleosols.
Keywords: Siwaliks; Mio-Pliocene; Paleosols; Geochemistry; Climate; Himalaya